Composition of Spermatophyta (Seed Plants) in the Biological Greenhouse Area of Univet Bantara Sukoharjo - Nugroho, Anwari Adi; Cahyanti, Fiky Ariska; Fitriani, Rindi Diah Ayu; Wahyuni, Tri; Oktavianingtyas, Desty (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2022)
Spermatophyta is a seed plant with a very high diversity and is easily found in the surrounding environment. The purpose of this study was to determine the composition of Spermatophyta in the biological greenhouse of the Univet Bantara Sukoharjo. Research This research is exploratory description research with the cruising method (survey). The research was conducted in the biology greenhouse of the Univet Bantara Sukoharjo campus which has an area of about 350 m2. The research procedure consisted of several stages, namely the preparation of tools and materials, observation and documentation of Spermatophyta in the greenhouse, recording of plant characteristics, identification and determination of plants, and data analysis. determination result. The plants data collected were analyzed descriptively and qualitatively. The results showed that the composition of Spermatophyta in the biological greenhouse was 58 species and all of them were angiosperms group which included dicotyledonous and monocotyledonous plants. The number of families found was 40 families. These results indicate that the biological greenhouse is not dominated by a few families but many families that live in the area. Families with more than one species are the Araceae family (talas taro tribe) with 6 species, the Euphorbiaceae family with 4 species, Papilionaceae and Asparagaceae each with 3 species, Mimosaceae, Amaranthaceae, Myrtaceae, Rutaceae, Oxalidaceae, and Orchidaceae were found 2 species. The diversity in the composition of spermatophytes in terms of their families is quite diverse, but the number of species from each family is not large enough so that further development is needed to enrich the diversity of Spermatophyta compositions in the biological greenhouse.